Extracellular signal-regulated kinase phosphorylation enhancement and NaV1.7 sodium channel upregulation in rat dorsal root ganglia neurons contribute to resiniferatoxin-induced neuropathic pain: The efficacy and mechanism of pulsed radiofrequency therapy. (31st March 2022) - Hidaka, Kotaro; Maruta, Toyoaki; Koshida, Tomohiro; Kurogi, Mio; Kage, Yohko; Kouroki, Satoshi; Shirasaka, Tetsuro; Takeya, Ryu; Tsuneyoshi, Isao
Pulsed radiofrequency (PRF) therapy is one of the most common treatment options for neuropathic pain, albeit the underlying mechanism has not been hitherto elucidated. In this study, we investigated the efficacy and mechanism of PRF therapy on resiniferatoxin (RTX)-induced mechanical allodynia, which has been used as a model of postherpetic neuralgia (PHN). Adult male rats were intraperitoneally injected with a vehicle or RTX. Furthermore, PRF current was applied on a unilateral sciatic nerve in all RTX-treated rats. On both ipsilateral and contralateral sides, the paw mechanical withdrawal thresholds were examined and L4-6 dorsal root ganglia (DRG) were harvested. In the DRG of rats with RTX-induced mechanical allodynia, NaV 1.7, a voltage-gated Na + channel, was upregulated following the enhancement of extracellular signal-regulated kinase phosphorylation. Early PRF therapy, which was applied 1 week after RTX exposure, suppressed this NaV 1.7 upregulation and showed an anti-allodynic effect; however, late PRF therapy, which was applied after 5 weeks of RTX exposure, failed to inhibit allodynia. Interestingly, late PRF therapy became effective after daily tramadol administration for 7 days, starting from 2 weeks after RTX exposure. Both early PRF therapy and late PRF therapy combined with early tramadol treatment suppressed NaV 1.7 upregulation in the DRG of rats with RTX-induced mechanical allodynia. Therefore, NaV 1.7 upregulation in DRG is related to the development of RTX-induced neuropathic pain; moreover, PRF therapy may be effective in the clinical management of patients with PHN via NaV 1.7 upregulation inhibition.